Pengaruh Komunikasi, Kompetensi, dan Gaya Kepemimpinan terhadap Kinerja Karyawan melalui Komitmen Organisasi sebagai Variabel Intervening (Studi pada Karyawan BRT Trans Jateng Koridor Semarang – Bawen) - Riza Halida Nafiha; Nunik Kusnilawati; Indarto Indarto (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of communication, competence, and leadership style on employee performance through organizational commitment as an intervening variable for Trans Jateng BRT employees on the Semarang–Bawen Corridor. The research method used a quantitative approach with explanatory research. Data were obtained by distributing questionnaires to Trans Jateng BRT drivers and service personnel using a five-point Likert scale. The data analysis technique used Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with the help of SmartPLS 4.1.1.0 to test the direct and indirect effects between variables. The results showed that communication and competence significantly influenced employee performance, while leadership style did not. Communication significantly influenced organizational commitment, while competence and leadership style did not significantly influence organizational commitment. Organizational commitment significantly influenced employee performance and was able to mediate the influence of communication on performance, but did not mediate the influence of competence and leadership style on performance. The conclusion of this study indicates that improving Trans Jateng BRT employee performance is more effective through strengthened communication that builds organizational commitment, accompanied by increased competency. However, leadership style has not yet become a primary determining factor in a standardized operational context.   Keywords: Communication, Competence, Leadership Style, Organizational Commitment, Employee Performance